The histone methyltransferase Suv39h regulates 3T3-L1 adipogenesis. (1st January 2020) - Jing, Jia; Li, Fenfen; Zha, Lin; Yang, Xiaosong; Wu, Rui; Wang, Shirong; Xue, Bingzhong; Shi, Hang
ABSTRACT: We discovered a unique expression pattern of two histone methyltransferases Suv39h1 and Suv39h2 during 3T3-L1 adipogenesis, both of which preferentially catalyse the formation of H3K9 dimethylation (H3K9me2) and further H3K9 trimethylation (H3K9me3), a transcriptional repressive mark. The expression of Suv39h1 and Suv39h2 displayed a sharp increase at the early stage of 3T3-L1 differentiation, which peaked after differentiation induction, and then declined towards later stage of differentiation, suggesting a key role for these two histone methyltransferases in adipogenesis. Indeed, inactivating Suv39h1 or Suv39h2 via lentiviral shRNA knockdown inhibited adipogenesis, while overexpressing Suv39h1 promoted adipogenesis. Notably, overexpressing or knocking down Suv39h1 in 3T3-L1 cells was associated with reciprocal changes in the expression of Wnt10a, an anti-adipogenic regulator. Further, Wnt10a knockdown largely prevented the inhibitory effect of Suv39h1 on adipogenesis, indicating Wnt10a as a downstream target mediating Suv39h1's action in adipogenesis. Mechanistically, our comprehensive approaches involving ChIP, co-immunoprecipitation and pyrosequencing analysis demonstrated that Suv39h1 may regulate Wnt10a expression via H3K9 methylation and interaction with DNA methyltransferase 1 (DNMT1) at the Wnt10a promoter, resulting in altered DNA methylation at the promoter. We conclude that Suv39h promotes adipogenesis by epigenetically down-regulating Wnt10a expression via H3K9me3 and DNA methylation at the Wnt10a promoter.Abbreviated title: Suv39h and 3T3-L1 Adipogenesis